Research Site Anonymity in Context. (December 2022) - Nduna, Mzikazi; Mayisela, Simangele; Balton, Sadna; Gobodo-Madikizela, Pumla; Kheswa, Jabulani G.; Khumalo, Itumeleng P; Makusha, Tawanda; Naidu, Maheshvari; Sikweyiya, Yandisa; Sithole, Sello L.; Tabane, Cily
This paper utilizes critical theory to interrogate and problematize the practice of anonymising research sites as an ethical imperative. The contributing authors conduct research in and with various communities in southern Africa, position themselves and work from and within diverse areas and specialities of the social sciences. This article is developed from their rich and wide spectrum of field experience with a great diversity of communities, but mainly the poorer, under-resourced, socially and economically marginalized. The authors strongly identify with these communities whose anonymity in published research is seen as marginalizing. Such research sites are places and communities where these researchers grew up and live in, and thus not just as peripheral or 'out there' entities. Therefore, the naming of research sites in this context is deemed as being ethical, out of respect for participants, for a contextually embedded understanding, and for well-targeted interventions and policy influence.